Factors influencing employee performance at peace corps of Nigeria - Vincent, Aniekwena Egbuna (2022)
The study aims to examine the influence of job satisfaction, supervisor support, physical work environment and employee motivation on employee performance. The employees at peace corps of Nigeria Abuja headquarters, Lagos and Anambra state offices were considered. The headquarters and 2 state offices which constitute a total of 4000 employees of peace corps of Nigeria as the population were involved in this analysis. This study made use of quantitative method and cross-sectional research design. 702 questionnaires were distributed online via google form and 376 collected and analyzed with the use of Statistical Package for Social Sciences (SPSS) 20.0 version. Descriptive analysis was applied in evaluating the demographic profile (age, gender, marital status, level of education, job rank, year in service). Correlation as well regression was employed to analyze the relationship between job satisfaction, supervisor support, physical work environment, employee motivation and employee performance. The outcome of this study depicted that with exception of physical work environment which has insignificant relationship with employee performance, job satisfaction, supervisor support and employee motivation are significantly correlated with employee performance. This implies that the independent variables examined in this study impacts employee’s resolve to continue working in the organization.